Advanced Farming Using Smart Technology - Gireesh Babu, CN; Chandra Shekhara, KT; Kavitha, SA; Chethan, DN (International Journal of Computer Sciences and Engineering, 2025)
This paper describes a new approach for advanced farming in agricultural management using Internet-of-Things, Mobile-Computing and Big-Data analytics. Farmers, marketing agencies and vendors need to be registered to the Farm-Cloud module through Mobile-App module. Farm-Cloud storage is used to store the details of farmers, soil properties of farmlands, vendors and marketing agencies, e-governance schemes and current environmental conditions. Soil and environment conditions are sensed and periodically sent to Farm-Cloud through IOT. Big-data analysis on Farm-Cloud data is done for fertilizer requirements, best crop sequences analysis, total production, and current stock and market requirements. Data Mining is used to solve the queries of vendors, farmers and marketing agencies through Farm-Cloud. Sensors are used to sense the details regarding the soil and its properties of the farmland and sends it to the Farm-Cloud. Proposed model is beneficial for increase in agricultural production and for cost control of products.